Teacher Quality at the High School Level: The Importance of Accounting for Tracks - Jackson, C. Kirabo (Journal of Labor Economics, 2014)
Unlike in elementary school, high school teacher effects may be confounded with both selection to tracks and track-level treatments. I document confounding track effects and show that traditional tests for the existence of teacher effects are biased. After accounting for biases, high school algebra and English teachers have smaller test score effects than found in previous studies and value-added estimates are weak predictors of teachers’ future performance. Results indicate that either (a) teachers are less influential in high school than in elementary school or (b) test score effects are a weak measure of teacher quality at the high school level.